(untitled) (Al-Academy, 2024)
The research reveals patterns and methods of displaying formal organizations in the design achievement, and the research included four chapters. The first chapter (the methodological framework) revealed the research problem and the researcher’s question about the study problem was identified as follows: - What is the role of formal organization in environmental awareness poster designs? The importance of the research lies in contributing to the selection and construction of the idea according to formal organizational criteria and its enhancement of visual perception. The aim is to uncover the role of these organizations, define the temporal, spatial, and objective boundaries, followed by defining the terms and their procedural definition. The second chapter (the theoretical framework) contained two sections: - The role of communication, form, and concepts in graphic design. The second chapter was completed with indicators and a comparison between the previous study and the current study. Then came the third chapter, which dealt with research procedures. As for the fourth and final chapter, it included the research results, among the most prominent: The formal organization represented by the central and focal pattern is predominant in educational design and is one of the most commonly used systems in the final output of educational graphic design. The fourth chapter also included several conclusions, among the most important: - 1. Adopting varied patterns in the formal system for elements within the poster space leads to competition between visual attraction and achieving dominance for shapes. At the end of the research, a list of sources, shapes, and diagrams was attached